Step-by-step explanation:
Hey there!
Given;
f ( x ) = x² + 2x - 1
g ( x ) = 3x - 2
To verify:

LHS:

~ Insert "2" instead of "x".

Simplify it;

Therefore; (f/g)(2) = 7/4.
RHS:

~Insert "2" instead of"x".

Simplify it.

Therefore, f(2)/g(2) = 7/4.
Since (f/g)(2) = f(2)/g(2) = 7/4.
<em><u>Proved!</u></em>
<u>Hope </u><u>it </u><u>helps</u><u>!</u>
First, let's add 30 to both sides:
4x - 30 +30 ≥ -3x + 12+30
4x ≥ -3x + 42
Now, let's add 3x to both sides
4x +3x ≥ -3x+3x + 42
7x ≥ 42
Let's divide both by 7:
x ≥ 6
Answer: 64 lbs
Step-by-step explanation:
I divided 56/140 and got 0.4. Then multiplied 0.4 by 160 and got 64. SOunds about right to me.
You can double check by multipling 0.4 by 140 and you get 56.
The answer is -8. Just plug in the options for x and add both up to get the full length of the line which is 15